Patterns of Self-Medication in Primary Dysmenorrhea among Nursing Students of Patan Academy of Health Sciences - Gupta, Mayuri; Joshi, Mili; Aryal, Sushant; Shrestha, Ram Krishna; Kafle, Sajala; Shakya, Tripti (Nepal Medical College Journal, 2025)
Dysmenorrhea is a common periodic menstrual pain in young women without pelvic pathology characterized by lower abdominal cramps, starting within the first 8 to 72 hours of menstruation. A descriptive, cross-sectional study was conducted among 153 nursing students. They were selected by enumerate sampling technique. Data were collected through a self-administered questionnaire. Point estimate and 95.0% confidence interval were calculated. Among 153 nursing students, 145 had primary dysmenorrhea and self-medication was found in 88 (57.52%) students. Among all the self-medications, paracetamol was most common which was used by 40 (26.1%) students, followed by Mefenamic acid, in 36 (23.5%) students. The prevalence of self-medication in primary dysmenorrhea among undergraduate students was lower. Therefore, health professional consultation must be promoted to help students with dysmenorrhea.